Risk perceptions of dust and its impacts among communities living in a mining area of the Witwatersrand, South Africa - Wright, C.Y.; Matooane, M.; Oosthuizen, M.A.; Phala, N. (Clean Air Journal = Tydskrif vir Skoon Lug, 2014)
Mining is a major economic activity in many developing countries. In South Africa, gold mining has played a significant role in the development and sustenance of the country's economy, with both positive and negative consequences. In gold mining areas, tailings dams and mine dumps are significant sources of ambient dust, known to be a nuisance, and health risk, to communities living near them and who must find appropriate coping mechanisms to protect themselves. A qualitative study based on five focus groups with sixty-two participants of different ages and sex was carried out in the Witwatersrand mining district of South Africa. All focus groups agreed that they had noticed dust in the air where they live, stating that the dust came largely from mine dumps but also from other sources. They agreed that the dust causes, among others, health problems, and both short-term and long-term coping mechanisms for protecting themselves against excess dust were mentioned yet considered inadequate, i.e. closing windows and doors, watering their yards, paving their yards and planting trees. Little support from government, mines and other organisations was identified as an important perceived barrier to resolving the dust problem. Means for communication of communities' perceptions of the impacts, risks and possible mitigation / adaption measures associated with dust need to be created and supported in a formal risk management plan.